E-pénz – helyi pénz - Gál, Veronika Alexandra; Gáspár Bencéné Vér, Katalin (Acta Scientiarum Socialium, 2013)
E-money – local money The local currencies that have been issued in Hungary used to be paper-money substitutes. The production costs of banknotes (and coins as well) are usually high and due to the natural wearing out replacement is needed which means new printing and other costs. Our article is looking for the answer for the question whether local currency could be issued as electronic money. First of all, it is necessary to examine the purpose and function of the local cur-rency and to see by whom, where and for what kind of shopping the currency is used. Electronic money issue is brought under regulation. Acceptation of e-money has several IT conditions. Could the goals of local currency issue be achieved by e-money? Would the local money in electronic form have any advantage in accounting techniques? These and similar questions have to be answered before any local currency is issued in electronic form. Based on our analysis we concluded that the local currency as electronic money may be issued. In our opinion the best form for this may be the electronic purse.
Keywords: local currency/money; electronic money; e-money